Financial Inclusion and Bank Stability in Selected SADC Countries - Jeke, Leward (International Journal of Economics and Financial Issues, 2024)
Financial inclusion is very critical in every country and has recently become a policy agenda for economic stability. A number of studies have suggested both positive and negative ways in which financial inclusion could affect financial stability, but very few empirical studies have been made of their relationship. However, there seems to be a lack of consensus across the literature on the effect of financial inclusion on bank stability especially in developing countries. Given the different empirical views, the aim of this study is to examine the effect of financial inclusion on bank stability in selected SADC countries. The study findings reveal that financial inclusion has a significant positive relationship with bank stability (z-score). The study also found a significant negative effect of bank efficiency on bank stability. Policymakers should ensure financial literacy for all to reduce bank fragility. They should also find ways of enhancing bank competition which reduces non-performing loans and bank insolvency. On practical implications, the study calls for the complementation of financial inclusion with financial literacy to enhance bank stability.